New [3+2+1] Iridium Complexes as Effective Phosphorescent Sensitizers for Efficient Narrowband Saturated–Blue Hyper–OLEDs - Chengcheng Wu; Kai‐Ning Tong; Kefei Shi; Zhaoyun Jin; Yuan Wu; Yingxiao Mu; Yanping Huo; Man‐Chung Tang; Chen Yang; Hong Meng; Feiyu Kang; Guodan Wei (Advanced Science, 2023)
Abstract Two newly designed and synthesized [3+2+1] iridium complexes through introducing bulky trimethylsiliyl (TMS) groups are doped with a terminal emitter of v–DABNA to form an coincident overlapping spectra between the emission of these two phosphors and the absorption of v–DABNA, creating cascade resonant energy transfer for efficient triplet harvesting. To boost the color quality and efficiency, the fabricated hyper‐OLEDs have been optimized to achieve a high external quantum efficiency of 31.06%, which has been among the highest efficiency results reported for phosphor sensitized saturated‐blue hyper‐OLEDs, and pure blue emission peak at 467 nm with the full width at half maxima (FWHM) as narrow as 18 nm and the CIEy values down to 0.097, satisfying the National Institute of Standards and Technology (NIST) requirement for saturated blue OLEDs display. Surprisingly, such hyper‐OLEDs have obtained the converted lifetime (LT50) up to 4552 h at the brightness of 100 cd m−2, demonstrating effective Förster resonance energy transfer (FRET) process. Therefore, employing these new bulky TMS substituent [3+2+1] iridium(III) complexes for effective sensitizers can greatly pave the way for further development of high efficiency and stable blue OLEDs in display and lighting applications.